2011
DOI: 10.1186/bcr2922
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EpCAM positive cells isolated from sentinel lymph nodes of breast cancer patients identifies subpopulations of cells with distinct transcription profiles

Abstract: IntroductionThe presence of tumor cells in the axillary lymph nodes is the most important prognostic factor in early stage breast cancer. However, the optimal method for sentinel lymph node (SLN) examination is still sought and currently many different protocols are employed. To examine two approaches for tumor cell detection we performed, in sequence, immunomagnetic enrichment and RT-PCR analysis on SLN samples from early stage breast cancer patients. This allowed us to compare findings based on the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Neither in DG75 CBF1 wt nor in DG75 CBF1 ko cells statistically significant changes (p ≤ 0.05) of cellular transcript abundance in response to estrogen treatment were observed, proving that target gene activation is strictly dependent on ER/EBNA2 (S1A Fig). In addition, estrogen responsive target genes described in the literature did not change expression levels proving that the estrogen receptor response is not functional in DG75 B cells (S1B Fig) [2327]. It is important to note that EBNA2 not only activates a set of direct target genes but thereby initiates a cascade of secondary events, which are included in our target gene lists and in total reflect EBNA2 functions.…”
Section: Resultsmentioning
confidence: 99%
“…Neither in DG75 CBF1 wt nor in DG75 CBF1 ko cells statistically significant changes (p ≤ 0.05) of cellular transcript abundance in response to estrogen treatment were observed, proving that target gene activation is strictly dependent on ER/EBNA2 (S1A Fig). In addition, estrogen responsive target genes described in the literature did not change expression levels proving that the estrogen receptor response is not functional in DG75 B cells (S1B Fig) [2327]. It is important to note that EBNA2 not only activates a set of direct target genes but thereby initiates a cascade of secondary events, which are included in our target gene lists and in total reflect EBNA2 functions.…”
Section: Resultsmentioning
confidence: 99%
“…There have been several studies showing that this inflammation was associated with cancer progression. Many authors have shown that inflammation can enhance tumor cell proliferation, invasion, angiogenesis, and eventual metastasis [17,18,19,20,21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Surgery-induced inflammation could induce tumor growth, modify the immune response, and even exacerbate tumor dissemination [17,18,19,20,21,22,23,24]. Therefore, we hypothesized that the inflammation induced by surgery could impact the clinical outcome in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of metastatic cells in the lymph node or circulating tumor cells (CTCs) in the peripheral blood is strongly associated with poor clinical outcome in breast cancer [41-43]. AGR2 may be a fitting target for detection of metastatic cells as it has been found to promote metastasis in functional experiments and to be expressed in metastatic breast cancer cells in humans.…”
Section: The Role Of Agr2 In Breast Cancermentioning
confidence: 99%